A novel missense mutation in F9 gene causes hemophilia B in a family with clinical variability. Issue 2 (March 2020) - Yi, Sheng; Yang, Qi; Zuo, Yangjin; Li, Mengting; Luo, Jingsi; Qin, Zailong; Zhang, Qinle; Li, Meng; Huang, Limei; Lu, Yingchi; Feng, Shihan; Fan, Xin
Abstract : N/A: Hemophilia B is an X-linked recessive bleeding disorder caused by diverse mutations throughout the F9 gene. The same F9 mutation may result in different degrees of clotting factor deficiency. The aim of this study was to investigate the pathogenesis of two hemophilia B patients with different severity in a family. A family with two hemophilia B patients was recruited in this study. Coagulation assays, activities of FVIII (FVIII:C) and FIX (FIX:C) were evaluated. All of the exons and intron exon boundaries of the F9 gene were amplified by PCR and analyzed by direct sequencing. The proband, 12-year-old boy with moderate bleeding history, had manifest prolonged activated partial thromboplastin time (98.1 s) and markedly decreased FIX activity (1%). His maternal uncle presented slightly prolonged activated partial thromboplastin time (48.2 s) and mildly decreased FIX activity (15.2%). Molecular genetic analysis of F9 revealed that they were hemizygous for a novel missense mutation, c.157G>C (p.Glu53Gln). Our study widens the mutation spectrum of the FIX gene. In addition, this report provides a specific case associated with genotype and phenotype heterogeneity of hemophilia B.